Selective MicroRNA-Offset RNA Expression in Human Embryonic Stem Cells - Asikainen, Suvi; Heikkinen, Liisa; Juhila, Juuso; Holm, Frida; Weltner, Jere; Trokovic, Ras; Mikkola, Milla; Toivonen, Sanna; Balboa, Diego; Lampela, Riina; Icay, Katherine; Tuuri, Timo; et al. (PloS one, 2015)
Small RNA molecules, including microRNAs (miRNAs), play critical roles in regulating pluripotency, proliferation and differentiation of embryonic stem cells. miRNA-offset RNAs (moRNAs) are similar in length to miRNAs, align to miRNA precursor (pre-miRNA) loci and are therefore believed to derive from processing of the pre-miRNA hairpin sequence. Recent next generation sequencing (NGS) studies have reported the presence of moRNAs in human neurons and cancer cells and in several tissues in mouse, including pluripotent stem cells. In order to gain additional knowledge about human moRNAs and their putative development-related expression, we applied NGS of small RNAs in human embryonic stem cells (hESCs) and fibroblasts. We found that certain moRNA isoforms are notably expressed in hESCs from loci coding for stem cell-selective or cancer-related miRNA clusters. In contrast, we observed only sparse moRNAs in fibroblasts. Consistent with earlier findings, most of the observed moRNAs derived from conserved loci and their expression did not appear to correlate with the expression of the adjacent miRNAs. We provide here the first report of moRNAs in hESCs, and their expression profile in comparison to fibroblasts. Moreover, we expand the repertoire of hESC miRNAs. These findings provide an expansion on the known repertoire of small non-coding RNA contents in hESCs.